Indonesian Prospect of Economy Post COVID-19 Crises Using The Model of AbdulHamid Abu Sulayman’s Cultural Progress - Atikah Inayah; Alde Mulia Putra; Ali Musa Harahap (Dauliyah: Journal of Islam and International Affairs, 2024)
Many previous studies claimed that halal certification is one of the keys to economic escalation especially during COVID-19 crises. However, the facts show that no international regime or organization has yet gathered this need to strengthen  economic opportunities for countries supporting the halal industry. For this reason, due to the absence of an international halal assembly which is can be the law protection for halal certification, this research hold a study related to one of the bodies under the Organization Islamic Cooperation (OIC), namely SMIIC or Standards and Metrology Institute for Islamic Countries, which is also an international halal regime with a focus on standardization. This research aims to analyze the significance of the international regime, namely the SMIIC on the awareness of the halal certification in Indonesia as the manifestation of AbdulHamid’s epistemological idea of cultural progress. This research also examined some challenges from the unit of analysis and proposed some recommendation. Keywords: COVID-19, Halal, Indonesia, International Regime, Islam.